2020
DOI: 10.1111/mam.12229
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal and seasonal plasticity in American bison Bison bison diets

Abstract: In ecological niche theory, diet is a trait frequently used to place species along a continuum from specialists to generalists. A multidimensional approach to investigating species’ niches has been developed to incorporate nutrition. We apply the concepts of multidimensional nutritional niche theory to the dietary patterns of a widespread, large herbivore, the American bison Bison bison, at various levels of its nutritional niche. Specifically, we sought to estimate dietary niches for female bison at the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Herbivore nutritional quality is typically defined in terms of energy, concentration of limited nutrients (i.e., protein), and limiting factors such as digestibility (i.e., structural carbohydrates’ concentration), all of which influence herbivore fitness (Hamel et al, 2012 ; Plumb et al, 2009 ; van Soest, 1994 ). Forbs and browse tend to have greater quantities of limited nutrients than graminoids, and graminoids have more structural carbohydrates, regardless of season (Craine et al, 2010 ; Hecker et al, 2021 ). The nutritional niche of herbivores has been estimated using a multidimensional approach known as nutritional geometry (Machovsky‐Capuska et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbivore nutritional quality is typically defined in terms of energy, concentration of limited nutrients (i.e., protein), and limiting factors such as digestibility (i.e., structural carbohydrates’ concentration), all of which influence herbivore fitness (Hamel et al, 2012 ; Plumb et al, 2009 ; van Soest, 1994 ). Forbs and browse tend to have greater quantities of limited nutrients than graminoids, and graminoids have more structural carbohydrates, regardless of season (Craine et al, 2010 ; Hecker et al, 2021 ). The nutritional niche of herbivores has been estimated using a multidimensional approach known as nutritional geometry (Machovsky‐Capuska et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…We chose bison because they have been described as obligate grazers and have the morphophysiology of a grazer (Hofmann, 1989 ; Strong & Gates, 2009 ). However, recently, forbs and browse have been found to contribute significant proportions to some bison diets, especially during summer (Bergman et al, 2015 ; Craine et al, 2015 ; Hecker et al, 2021 ; Leonard et al, 2017 ). We elected to examine the diets of females because female bison are known to have higher quality diets that are more diverse in composition than males (Jung, 2015 ; Mooring et al, 2005 ; Popp, 1981 ).…”
Section: Introductionmentioning
confidence: 99%
“…The success of these projects demonstrates that bison are clearly adapted to thrive in a broad range of climates, vegetation conditions, and predators, even if snow depth [40], forage quality and availability [105] and non-human predation [106] influence their localized spatial distribution. Recent studies have also demonstrated remarkable plasticity in bison diets across North America [107,108], providing further evidence that bison can thrive in a variety of conditions. Lastly, MaxEnt ecological niche modelling based on fossil records of bison and historic climates demonstrated that much of North America was suitable bison habitat over the past 20,000 years [30].…”
Section: Implications For Bison Restoration In the Western Cordilleramentioning
confidence: 88%
“…The success of these projects demonstrates that bison can thrive in a broad range of climates, vegetation conditions, and predators, even if snow depth [48], forage quality and availability [116] and non-human predation [117] influence their localized spatial distribution. Recent studies have also demonstrated remarkable plasticity in bison diets across North America [118,119], and MaxEnt ecological niche modelling based on fossil records of bison and historic climates demonstrated that much of North America was suitable bison habitat over the past 20,000 years [13].…”
Section: Implications For Bison Restoration In the Western Cordilleramentioning
confidence: 99%